2002
DOI: 10.3354/meps226143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of settlement patterns of red drum Sciaenops ocellatus larvae to estuarine nursery habitat: a stable isotope approach

Abstract: A novel approach was used to study the settlement of red drum Sciaenops ocellatus larvae from the coastal Gulf of Mexico to a seagrass meadow in the Aransas Estuary, Texas, during an entire recruitment season (September through November 1999). Differences in the δ 13 C and δ 15 N of the food webs supporting red drum while in the planktonic and estuarine habitats were characterized and used to identify post-settlement individuals in the process of completing the isotopic shift between the planktonic and estuari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…These values are consistent with the bulk δ 13 C signatures of zooplankton (Fig. 3) and are typically planktonic in lagoon and coastal food webs, taking into account a slight 13 C depletion in lipids relative to bulk tissue (Herzka et al 2002, Pepin & Dower 2007. We are therefore confident that the smallest size class was representative of the marine-planktonic phase of Liza saliens juveniles.…”
Section: Discussion δ δ 13 C Values Of Individual Fassupporting
confidence: 74%
See 1 more Smart Citation
“…These values are consistent with the bulk δ 13 C signatures of zooplankton (Fig. 3) and are typically planktonic in lagoon and coastal food webs, taking into account a slight 13 C depletion in lipids relative to bulk tissue (Herzka et al 2002, Pepin & Dower 2007. We are therefore confident that the smallest size class was representative of the marine-planktonic phase of Liza saliens juveniles.…”
Section: Discussion δ δ 13 C Values Of Individual Fassupporting
confidence: 74%
“…It is believed that the reduced water turbulence in the benthos results in a thicker boundary layer around benthic algae, restricting the diffusion rate of CO 2 or HCO 3 -, with subsequent reduced discrimination against 13 C (France 1995). In coastal environments, this phenomenon may generate a mean δ 13 C enrichment of 5 ‰ or more in benthic algae (including epiphytes) relative to phytoplankton (France 1995, Herzka et al 2002, Jaschinski et al 2008, Vinagre et al 2008. However, the plankton-like FA δ 13 C values of > 200 mm fish were quite surprising, and suggested that young adult L. saliens, which are supposed to have a similar diet to settled juveniles, occupy a distinct isotopic niche.…”
Section: Discussion δ δ 13 C Values Of Individual Fasmentioning
confidence: 99%
“…According to stable isotope analysis, larvae switch from a diet of particulate organic matter endmembers (pelagic and detrital) to a diet of marsh plants and macroalgae end-members (benthic) at around 6 to 8 mm SL (Herzka et al 2002). This indicates that larvae change their diet relatively rapidly after entering the estuaries, although our experiments suggest they might not utilize the substrate fully until approximately 12.5 mm SL.…”
Section: Discussionmentioning
confidence: 71%
“…For fishes that use different habitats for each life phase, this 3-phase life cycle decouples reproduction from recruitment of new individuals into the local population. This is especially true for fish taxa with larvae that settle into benthic habitats that are distinct from those of adults (Shulman & Ogden 1987, Eggleston 1995, Peters et al 1998, Herzka et al 2002, Shenker et al 2002, creating 2 stages within the demersal phase of life history. Examination of the processes affecting each of these life stages, and the connections between life stages, is essential to developing a better understanding of ontogenetic habitat requirements of fishes.…”
Section: Introductionmentioning
confidence: 99%